Galleria mellonella as an infection model to investigate virulence of Vibrio parahaemolyticus. Issue 1 (1st January 2018) - Wagley, Sariqa; Borne, Richard; Harrison, Jamie; Baker-Austin, Craig; Ottaviani, Donatella; Leoni, Francesca; Vuddhakul, Varaporn; Titball, Richard W.
ABSTRACT: Non-toxigenic V. parahaemolyticus isolates ( tdh − / trh − /T3SS2 − ) have recently been isolated from patients with gastroenteritis. In this study we report that the larvae of the wax moth ( Galleria mellonella ) are susceptible to infection by toxigenic or non-toxigenic clinical isolates of V. parahaemolyticus . In comparison larvae inoculated with environmental isolates of V. parahaemolyticus did not succumb to disease. Whole genome sequencing of clinical non-toxigenic isolates revealed the presence of a gene encoding a nudix hydrolase, identified as mutT . A V. parahaemolyticus mutT mutant was unable to kill G. mellonella at 24 h post inoculation, indicating a role of this gene in virulence. Our findings show that G. mellonella is a valuable model for investigating screening of possible virulence genes of V. parahaemolyticus and can provide new insights into mechanisms of virulence of atypical non-toxigenic V. parahaemolyticus . These findings will allow improved genetic tests for the identification of pathogenic V. parahaemolyticus to be developed and will have a significant impact for the scientific community.